The coroner's role in Peru - Fernández Dávila, Guillermo (1956)
Brilliant opportunity arises to expose, in a work of synthesis and assembly, all that has been done so far, and everything has to be done still, for Legal Medicine in Peru have a seat and a development in harmony with historical and ardent desires, with great tenacity and encouragement, appreciate this specialty as one of the greatest pleasures of his spirit backgrounds.